印尼慈育大学中文系一二年级学生综合课初级词汇教学研究 - Rina Maryana Goven; Juliana Gunawan; Malahayati Hazimah; Jesslyn Thea Lestari (Jurnal Asosiasi Program Studi Mandarin Indonesia (Jurnal APSMI), 2022)
摘要 词汇在学习外语当中有着非常重要的作用，在学习汉语的词汇时许多学习者会遇到一些困难。随着在印尼使用汉语言的发展和汉语学习者不断增加，学习汉语词汇的质量也有待提高，特别是在基础学习者学习汉语综合课里的词汇。在本研究中，作者运用认知语言学中的原型范畴理论，分析了中文系一二年级的学习者对学习和使用汉语词汇的掌握和理解能力尤其是在学综合课。本研究旨在找出学习者在学习综合课中的词汇时经常遇到的问题和困难。本研究成果有助于汉语学习领域的发展。本研究结果有望为提高学习汉语词汇的质量提供更具体的解决方案，特别是为一二年级的学习者在学习综合课里的词汇。 关键词: 中文；生词；综合课；一二年级学生；慈育大学  AbstractVocabulary has a very important role in learning foreign languages, many learners will encounter some difficulties when learning Chinese characters. With the development of the use of Chinese language in Indonesia and the increasing number of Chinese learners, the quality of learning Chinese vocabulary needs to be improved, especially for basic learners to learn vocabulary in comprehensive Chinese courses. In this study, the author uses the prototype category theory in cognitive linguistics to analyze the mastery and comprehension ability of the first- and second-year learners of the Chinese department in learning and using Chinese vocabulary, especially in comprehensive courses. The purpose of this study is to find out the problems and difficulties that learners often encounter when learning vocabulary in integrated lessons. The results of this research contribute to the development of the field of Chinese language learning. The results of this study are expected to provide more specific solutions for improving the quality of learning Chinese vocabulary, especially for first- and second-grade learners who are learning vocabulary in comprehensive courses. Keywords: Chinese language; Vocabulary; Comprehensive courses; First and second year students; Bunda Mulia University